Acute renal failure in a neonate due to bilateral primary obstructive megaureters - Shotaro Nakanishi; Minoru Miyazato; Ryota Miyagi; Seiichi Saito (Elsevier, 2018)
A male newborn was referred to our institute for postrenal acute renal failure with bilateral hydroureteronephrosis, electrolyte imbalance, and anuria. Voiding cystourethrography revealed no vesicoureteral reflux or posterior urethral valves. We performed bilateral percutaneous nephrostomy on the 9th post-natal day. The serum creatinine level improved to the normal range. Antegrade pyelography revealed bilateral uretero-vesical junction stenosis. Subsequently, we inserted bilateral double J urethral stents at 1 month. Bilateral ureteroneocystostomy without ureteral folding was performed at 6 months. The postoperative course was uneventful. This is the second case of postrenal acute renal failure with bilateral primary obstructive megaureters in a neonate. Keywords: Megaureter, Acute renal failure, Infant